HUBUNGAN ANTARA KUALITAS TIDUR DAN KUANTITAS TIDUR DENGAN PRESTASI BELAJAR MAHASISWA - Jaka ' Sarfriyanda; Darwin ' Karim; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Individuals are required to meet basic human needs, one of which is sleep. In young adults often experience sleep disturbances and changes in sleeping hours. This aims of this research was to identify the correlation between sleep quality and quantity of sleep with the learning achievement of students in School of Nursing, University of Riau. The design was descriptive correlational research with cross sectional approach. The sampling technique total sampling involving 197 respondents that was selected based on inclusion criteria. This research used questionnaire for the variable sleep quality and quantity of sleep, and the value of the test block for the variable of learning achievement. The univariate analysis was results showed 35(17,8%) of the respondents had a good sleep quality and 162(82,2%) respondents had poor sleep quality, and the results also showed of 197 respondents, as many as 95(48,2%) respondents had enough sleep quantity and 102(51,8%) respondents had less sleep quantity. Bivariate analysis was obtained by using mann-whitney test and the statistic showed p value for the quality of sleep (0.284) > alpha (0.05), so it was concluded there was no correlation between sleep quality with learning achievement. For statistical results quantity of sleep obtained p value (0.244) > alpha (0.05), it can be concluded there was no correlation between the quantity of sleep with learning achievement. For subsequent researchers are strongly advised to examine the factors that affect sleep quality and quantity of sleep PSIK UR students. Keyword: Sleep quality, quantity of sleep, archievement of students